Pemahaman Masyarakat tentang Kecerdasan Buatan: Peran Edukasi, Regulasi, dan Kolaborasi - Humairoh, Siti; Hasanah, Nurul; Nazri, Muhammad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Artificial Intelligence (AI) has become integral to various sectors; however, public understanding of this technology remains limited. This study explores the roles of government, educational organizations, and the community in enhancing AI's understanding and ethical implementation. Employing a mixed-methods approach, data were collected through a survey of 300 respondents, in-depth interviews with 15 officials and representatives from educational organizations, and focus group discussions with 30 participants. Results indicate that only 30% of respondents feel adequately informed about AI applications, while government policies lack clear regulations. Community involvement in education-based programs has effectively reduced the negative stigma associated with AI. These findings emphasize the importance of collaboration among all stakeholders to create a supportive environment for AI implementation. This research is expected to serve as a reference for developing more effective policies and educational programs related to AI in the future.